Puerol and pueroside derivatives from Pueraria lobata and their anti-inflammatory activity. (January 2023) - Sun, Ying-Jie; Cao, Shi-Jie; Liang, Feng-Ni; Li, Jin-Yan; Zhang, Xiang-Yu; Li, Wei; Ding, Li-Qin; Qiu, Feng
Abstract: Five undescribed puerols and puerosides and three known analogues were obtained from the roots of Pueraria lobata . Their structures were determined by comprehensive analysis of spectroscopic data and chemical methods. Since puerol D and puerol C were racemic compounds, resolved into their enantiomers, and their absolute configurations were determined by experimental and calculated ECD spectra. Six of the isolates were evaluated for their inhibitory activities on NO generation and the expression of inflammatory factors in the LPS-stimulated RAW 264.7 macrophage cells. The results showed that ( S )-puerol C, ( R )-puerol C, isokuzubutenolide A and kuzubutenolide A significantly decreased the NO production (IC50 values in the range of 16.87–39.95 μM). Meanwhile, ( S )-puerol C, isokuzubutenolide A and kuzubutenolide A also reduced the mRNA expression of inflammatory factors (TNF-α, IL-1β and IL-6). Graphical abstract: Five undescribed puerols and puerosides along with three known analogues were obtained from the roots of Pueraria lobata, most of them showed anti-inflammatory effects. Image 1 Highlights: Eight puerol and pueroside derivatives including five undescribed ones were isolated from the roots of Pueraria lobata. Previously undescribed compounds puerol D and puerol C were racemic compounds and resolved into their enantiomers. ( S )-Puerol C, ( R )-puerol C, isokuzubutenolide A and kuzubutenolide A showed obvious anti-inflammatory activity. ( S )-Puerol C, isokuzubutenolide A and kuzubutenolide A reduced the mRNA expression of inflammatory factors.